Diaphragmatic eventration with impending gangrenous organoaxial volvulus of the stomach: Role of timely intervention - Chirukandath, Ravindran; Sharath Kesavan Krishnan; Nimisha Chemmangattuvalappil Ramachandran; Safna Kunhikandilakath; Babu Pulluvileyil John; Nayanathara Parayarukottayil (Asian Journal of Medical Sciences, 2022)
Eventration of diaphragm is a rare entity and often is characterized by a developmental abnormality of the diaphragm musculature. The acute presentation of organoaxial volvulus with impending gangrene of stomach is a life-threatening event and requires emergency diagnosis and surgical intervention. A 45-year-old man visited our hospital for evaluation of upper abdominal discomfort. He had a feeling of fullness and discomfort in the upper abdomen for 3 years. These attacks lasted about 2 hours and were not usually severe but eventually presented with severe abdominal pain. The patient was explored as general condition was deteriorating. On exploration, it was found that there was huge organoaxial stomach volvulus with impending stomach gangrene. Emergency exploration, gastropexy, and plication of diaphragm was done. Early diagnosis and prompt intervention may avoid consequent gastric volvulus and complications,improving the overall outcome and mortality.